VISTA: A Target to Manage the Innate Cytokine Storm - ElTanbouly, Mohamed A.; Zhao, Yanding; Schaafsma, Evelien; Burns, Christopher M.; Mabaera, Rodwell; Cheng, Chao; Noelle, Randolph J. (Frontiers in Immunology, 2021)
In recent years, the success of immunotherapy targeting immunoregulatory receptors (immune checkpoints) in cancer have generated enthusiastic support to target these receptors in a wide range of other immune related diseases. While the overwhelming focus has been on blockade of these inhibitory pathways to augment immunity, agonistic trigger via these receptors offers the promise of dampening pathogenic inflammatory responses. V-domain Ig suppressor of T cell activation (VISTA) has emerged as an immunoregulatory receptor with constitutive expression on both the T cell and myeloid compartments, and whose agonistic targeting has proven a unique avenue relative to other checkpoint pathways to suppress pathologies mediated by the innate arm of the immune system. We present insights from very recent studies on the impact of VISTA agonistic targeting of myeloid cells, and potential therapeutic implications in the settings of hyperinflammatory responses such as cytokine storms, driven by dysregulated immune responses to viral infections (with a focus on COVID-19) and autoimmune diseases.